Investment project for the maintenance, renovation and modernization of the rolling stock of the Metro Collective Transport System (STC) - Sosa Castro, Miriam (2022)
This article presents an investment project to maintain, renovate and modernize the Metro STC rolling stock. This research is focused on alleviating public transportation precariousness, poor quality, and inadequacy in the Mexico City Metropolitan Area. The results suggest that the project is feasible in terms of economic and social impact. Socially, the following variables will be reduced: generalized travel and maintenance costs, CO2 emissions, and catastrophic risk. In financial terms, the net present value is positive, and the benefit/cost ratio is greater than 6. This project is of utmost importance in the present context and considering the recent tragic incident on line 12 of the Mexico City subway.